Assessment of older adults' acceptance of IEQ in nursing homes using both subjective and objective methods. (October 2021) - Zhan, Hanzhang; Yu, Jingyu; Yu, Rong
Abstract: Due to accelerated population ageing, the demand for nursing homes has greatly increased in China. As older adults spend most of the day indoors, it is of great importance to improve indoor environmental quality (IEQ) to provide a comfortable living environment for senior residents in nursing homes. Therefore, this study aims to investigate older adults' acceptance of the IEQ in nursing homes using both subjective and objective methods. A questionnaire survey was conducted to collect subjective acceptance levels regarding IEQ in nursing homes (including air temperature, relative humidity, indoor air quality (IAQ), visual environment, and acoustic environment). Objective data on five environmental parameters (i.e., air temperature, relative humidity, CO2 concentration, illuminance level, and noise level) were collected using a wireless sensor network (WSN) system. A machine learning predictive model was established to assess IEQ acceptance on the basis of the data from the questionnaire survey and the WSN. The results showed that subjective assessments on five aspects of IEQ and objective measurements on five environmental parameters were related to overall IEQ acceptance. Air temperature had the greatest impact on the overall IEQ acceptance, while visual environment and illuminance level had the least influence. The study offers useful information on improving IEQ in nursing homes and helping to enhance older adults' quality of life. Highlights: Older adults' acceptance of IEQ was investigated using logistic regression. Both subjective questionnaires and objective measurements were employed. Air temperature is the most influential contributor to the acceptance of IEQ. Regression results are different between subjective and objective methods.